Sobre el status gramatical del aspecto y sus relaciones con las propiedades temporales y accionales - Nowikow, Wiaczesła (Studia Romanica Posnaniensia, 2004)
The aim of this paper is to present the following three questions: a) the grammatical status of the Aspect; b) the relations of this category to temporal properties (Tense); c) the relations of the Aspect to actional properties (Aktionsart). The author makes a typological-comparative analysis of the above-mentioned categories and relations in the modern Spanih and Polish and explains the differences and coincidences between these languages in the matter of the temporality and aspectuality.